Study Analysis of Confidence Level on Slow Learner Students - Wanabuliandari, Savitri; Ardianti, Sekar Dwi; Gunarhadi, Gunarhadi; Rejekiningsih, Triana (Universitas Pendidikan Ganesha, 2021)
Confidence helps to see life from the positive side and helps to find new experiences. This self-confidence has not been well embedded in slow learner students. Slow learner students have low self-confidence. One of the reasons for low self-esteem is discrimination and bullying at school. The purpose of this study was to analyze the level of self-confidence of slow learner students. This study uses a quantitative research approach. The research method used is a survey method. The respondents of this study were slow learner students in grade IV who had gone through psychological tests. The number of slow learner students is five students based on psychological tests. Data collection techniques using observation and questionnaires. This study tested the validity of the data by using the credibility test. Testing the credibility of the data is done through triangulation and using reference materials. This study uses data analysis techniques Miles and Huberman models. Qualitative data analysis was carried out by reducing data, presenting data, and drawing conclusions/verification. The result of the research is that the teacher still does not understand the characteristics of the slow learner students. Slow learners feel that the teacher does not care. Slow learners do not understand the material taught by the teacher. Slow learner students tend to be quiet and look down while studying. The self-confidence analysis shows that all students are slow learners in the category of not being confident.